1974
DOI: 10.1002/1097-0142(197405)33:5<1230::aid-cncr2820330507>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assay of bleomycin: Inactivation, tissue distribution, and clearance

Abstract: Blood, urine, and tissue distributions of Bleomycin in animals and man were studied by microbiological assay using Bacillus subtilis ATCC 6633. Bleomycin was inactivated in vitro by a variety of tissues. Contact of Bleomycin with mouse intestinal or liver homogenates resulted in almost complete inactivation, whereas mouse plasma, kidney, lung, skin, and muscle produced lesser inactivation grossly in that order. Similar trends of inactivation were demonstrated by available human tissues. The present data do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 8 publications
0
54
0
Order By: Relevance
“…The reduction in Vc, which only occurs in patients receiving bleomycin, indicates that bleomycin does have an effect on the lung vasculature, but different from the effect of etoposide and cisplatinL The capillary changes observed usng nailfold capllary microscopic examination (Bellmunt et al, 1987), the reported cases of Raynaud's phenomenon (Vogelzang et al, 1981;Adoue et al, 1984), myocardial infarction (Samuels et al, 1987) and pulmonary veno-occlusive disease (Joselson et al, 1983) induced by bleomycin alone or in combination therapy also suggest direct effects of bleomycin on the vasculature. The efects of bleomycin occur predominantly in the hlng and skin vasculature, because these two orgns are, in contrast to other orgns such as the liver, deficient in bleomycin hydrolase which inactivates bleomycin (Ohnuma et al, 1974).…”
mentioning
confidence: 99%
“…The reduction in Vc, which only occurs in patients receiving bleomycin, indicates that bleomycin does have an effect on the lung vasculature, but different from the effect of etoposide and cisplatinL The capillary changes observed usng nailfold capllary microscopic examination (Bellmunt et al, 1987), the reported cases of Raynaud's phenomenon (Vogelzang et al, 1981;Adoue et al, 1984), myocardial infarction (Samuels et al, 1987) and pulmonary veno-occlusive disease (Joselson et al, 1983) induced by bleomycin alone or in combination therapy also suggest direct effects of bleomycin on the vasculature. The efects of bleomycin occur predominantly in the hlng and skin vasculature, because these two orgns are, in contrast to other orgns such as the liver, deficient in bleomycin hydrolase which inactivates bleomycin (Ohnuma et al, 1974).…”
mentioning
confidence: 99%
“…4C), prominent peaks appeared at fractions 34-36 (BLM A2) and at fractions 28-29 (BLM dA2). Additional peaks also were seen in the void volume (fractions [12][13][14] and at fractions 25-26. In liver tissue (Fig.…”
mentioning
confidence: 99%
“…In a study by Ohnuma (14), homogenates of various tissues were incubated with bleomycin, and drug inactivation was followed. Liver, intestine, spleen, plasma, kidney all contained more inactivation enzyme than skin and lung.…”
Section: Mechanismmentioning
confidence: 99%